Pemanfaatan Agregat Sungai Masanda dalam Campuran AC – WC dengan Bahan Pengisi Abu Buah Aren - Salma Borong Mallua'; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
One of the ingredients that can be used as a filler in the AC - WC mixture is palm fruit ash. The ease of obtaining palm fruit ash is one of the factors in choosing to use this material and can also provide beneficial value for palm tree fruit waste. Palm trees are plants that can be found in tropical areas such as in Indonesia. This study was conducted to determine the use of substitutes for palm fruit ash content which can improve the physical properties of the AC-WC paved mixture and find out changes in the physical properties of concrete asphalt due to the addition of palm fruit ash and how much the carrying capacity of the test object is. This study aims to determine the characteristic value of the AC-WC mixture if you use palm fruit ash as a filler and to determine the effect of palm fruit ash filler on the AC-WC mixture. Testing the characteristics of coarse, fine aggregates, fillers and asphalt is the method used in this study which then designed the composition of the AC- WC mixture on masanda river stones as well as Marshall immersion testing to obtain Residual Marshall Stability. The test results of Marshall Immersion on the AC-WC (Asphalt Concrete-Wearing Course) mixture can be seen at an asphalt content of 7% with a residual marshall stability value of 94.91%. which means that it has met the 2018 Bina Marga specification standard, which is ≥90%.